An assessment of the potential and impacts of winter water banking in the Sokh aquifer, Central Asia - Gracheva, I.; Karimov, Akmal A.; Turral, Hugh; Miryusupov, F. (Springer, 2009)
The dynamics of artificial recharge of winter surface flows coupled with increased summer groundwater use for irrigation in the Sokh aquifer (Central Asia) have been investigated. Water release patterns from the giant Toktogul reservoir have changed, as priority is now given to hydropower generation in winter in Kyrgyzstan. Winter flows have increased and summer releases have declined, but the Syr Darya River cannot pass these larger winter flows and the excess is diverted to a natural depression, creating a 40 ? 109m3 lake. A water balance study of all 18 aquifers feeding the Fergana Valley indicated the feasibility of winter groundwater recharge in storage created by summer abstraction. This modeling study examines the dynamics of the process in one aquifer over a 5-year period, with four scenarios: the current situation; increased groundwater abstraction of around 625 million (M) m3/year; groundwater abstraction with an artificial recharge of 144 Mm3/year, equivalent to the volume available in low flow years in the Sokh River; and with a larger artificial recharge of 268 Mm3/year, corresponding to high flow availability. Summer surface irrigation diversions can be reduced by up to 350 Mm3 and water table levels can be lowered.